2014
DOI: 10.3329/bjpt.v21i1.19264
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal and trichome diversity in <i>Senna</i> Mill. from Bangladesh

Abstract: Foliar epidermal characters of ten species of Senna Mill. found in Bangladesh are investigated. Anisocytic, anomocytic, paracytic, tetracytic and haxacytic stomata are found across the species. Anisocytic and paracytic stomata are common in all species. In addition to anisocytic and paracytic types, anomocytic stomata are found in Senna sophera and hexacytic stomata are observed in S. auriculata. Anticlinal wall is straight in S. alata, S. hirsuta, S. occidentalis, S. siamea and S. tora, curved in S. auriculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Leaf trichome study of Hyptis suaveolens [23] revealed the presence of two types of non-glandular trichomes (monocellular and multicellular) and three types of glandular trichomes (peltate, capitate type I and capitate type II). A study conducted on the foliar epidermal characters of ten Senna species and found that Stomatal types of anisocytic, anomocytic, paracytic, tetracytic and haxacytic were found across the species, glandular trichomes were observed in S. hirsuta and S. occidentalis, while non-glandular trichomes are dominant in the remaining species [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf trichome study of Hyptis suaveolens [23] revealed the presence of two types of non-glandular trichomes (monocellular and multicellular) and three types of glandular trichomes (peltate, capitate type I and capitate type II). A study conducted on the foliar epidermal characters of ten Senna species and found that Stomatal types of anisocytic, anomocytic, paracytic, tetracytic and haxacytic were found across the species, glandular trichomes were observed in S. hirsuta and S. occidentalis, while non-glandular trichomes are dominant in the remaining species [12].…”
Section: Resultsmentioning
confidence: 99%
“…As Metcalfe and Chalk [11] reported, leaves are considered as the most varied organ anatomically in angiosperms which provides a variety of anatomical features that can be employed as useful taxonomic characters. Foliar anatomical characters like stomata and trichomes are found instrumental in solving taxonomic problems and its significance have long been recognized by various workers [12].…”
Section: Introductionmentioning
confidence: 99%
“…The epidermic layer derives from many features such as stomata, trichomes, and other anatomical features of the leaf epidermis, which serve as helpful anatomical tools in plants (Ahmad et al 2010). Taxonomic problems have been widely solved using foliar anatomical characters such as stomata and trichomes (Begum et al 2014). Moreover, foliar epidermal traits are very important for studying systematics and characterization among subfamilies and tribes (Wetzel et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic significance of micromorphology and anatomy in delimitation of taxa and establishment of interspecific relationships are well documented (Tschan and Denk, 2012;Meng and Mao, 2013;Begum et al, 2014). Metcalfe and Chalk (1950) studied the anatomy of the family Boraginaceae and found setae (hairs), epidermal surface and cystoliths as diagnostic characters.…”
Section: Introductionmentioning
confidence: 99%